Severe pegaspargase hypersensitivity reaction rates (grade ≥3) with intravenous infusion vs. intramuscular injection: analysis of 54, 280 doses administered to 16, 534 patients on children's oncology group (COG) clinical trials. Issue 7 (3rd July 2018) - Burke, Michael J.; Devidas, Meenakshi; Maloney, Kelly; Angiolillo, Anne; Schore, Reuven; Dunsmore, Kimberly; Larsen, Eric; Mattano, Len A.; Salzer, Wanda; Winter, Stuart S.; Carroll, William; Winick, Naomi J.; et al.
Abstract: PEGylated asparaginase (pegaspargase) can be administered via intramuscular (IM) injection or intravenous (IV) infusion with a hypersensitivity reaction (HSR) incidence ranging 3–41%. We evaluated grade ≥3 HSRs when given IM vs. IV on six Children's Oncology Group (COG) leukemia trials (2003–2015) to determine differences in HSR rates. 54, 280 doses were administered to 16, 534 patients. Considering all doses of pegaspargase during induction, consolidation, and delayed intensification, grade ≥3 HSR rate with IM injection was 5.4% ( n  = 482/8981) compared to 3.2% for IV ( n  = 245/7553) ( p  < .0001). If only the second and third doses of pegaspargase were analyzed, where the majority of grade ≥3 HSRs occur, the rate following IM injection was 10.1% ( n  = 459/4534) compared to 5.0% ( n  = 222/4443) for IV ( p  < .0001). On standardized treatment protocols conducted by the COG during 2003–2015, grade ≥3 HSR rates to pegaspargase occurred less frequently with IV infusion than IM injection.